The relationships between structural and psychological empowerment and job satisfaction among nurses - Tahere Bonyad Karizme; Tayebe Rahimi Pordanjani; Ali Mohamadzadeh Ebrahimi (Tehran University of Medical Sciences, 2016)
Background & Aim: Job satisfaction is of the most fundamental components of mental health in every profession and one of the most important factors in career success. Therefore, identifying factors affecting job satisfaction is necessary. One of these factors is employee empowerment. This study aimed to determine the relationship between structural and psychological empowerment and job satisfaction among nurses. Methods & Materials: In this cross-sectional correlational study, the study population was all nurses working in public hospitals in Mashhad (N=4300) in 2015. The samples consisted of 340 nurses, were selected by multistage cluster sampling method. Participants were assessed by the Conditions of Work Effectiveness Questionnaire-II (CWEQ-II), Psychological Empowerment Questionnaire and Job Description Index (JDI). In order to analyze the data, Pearson's correlation coefficient and regression analysis were used through SPSS software v.19, and for validation stage, the confirmatory factor analysis were applied using AMOS software v.21. Results: Results showed that there is a significant multiple correlation between structural empowerment, psychological empowerment and job satisfaction (P<0.001, R2=0.286). Of the eight variables entered into the regression analysis using stepwise technique, three variables including meaningfulness (β=0.30, P<0.001), impact (β=0.25, P<0.001) and access to support (β=0.13, P<0.001) altogether predict 28.6% of the variance in job satisfaction. Conclusion: The results show the importance of psychological empowerment, the sense of meaningfulness, impact, and access to support as strong predictors of job satisfaction. So, providing the conditions needed for the empowerment of nurses is recommended to increase their job satisfaction and subsequently their efficiency and life satisfaction.